Samoa Early Grade Reading Assessment : Results Report - World Bank (World Bank, Washington, DC, 2019)
Early grade reading assessment (EGRA) is a simple instrument that measures foundational reading skills of early primary school students in grades (years) 1-3. The results are used to identify progress towards achieving reading fluency and comprehension, which are essential skills for learning and completing primary education. The overall purpose of Sāmoa early grade reading assessment (SEGRA) therefore is to provide an initial measurement of how well children are learning to read and write in their local language in the first three-year levels of primary schooling. This report summarizes the results of SEGRA conducted in Sāmoa from August 21 to September 7, 2017.